2017
DOI: 10.1038/leu.2017.64
|View full text |Cite|
|
Sign up to set email alerts
|

miR-194-5p/BCLAF1 deregulation in AML tumorigenesis

Abstract: Deregulation of epigenetic mechanisms, including microRNA, contributes to leukemogenesis and drug resistance by interfering with cancer-specific molecular pathways. Here, we show that the balance between miR-194-5p and its newly discovered target BCL2-associated transcription factor 1 (BCLAF1) regulates differentiation and survival of normal hematopoietic progenitors. In acute myeloid leukemias this balance is perturbed, locking cells into an immature, potentially ‘immortal’ state. Enhanced expression of miR-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 50 publications
1
57
0
Order By: Relevance
“…[13][14][15] Decreased expression of miR-194-5p has been reported in various types of malignancy, including glioma, hepatoma carcinoma, gallbladder carcinoma and acute myeloid leukaemia. [16][17][18][19] Overexpressed miR-194-5p in non-small-cell lung cancer suppresses cell migration, invasion and metastasis. 20 These reports indicate that miR-194-5p functions as a tumour suppressor in various human malignancies.…”
mentioning
confidence: 99%
“…[13][14][15] Decreased expression of miR-194-5p has been reported in various types of malignancy, including glioma, hepatoma carcinoma, gallbladder carcinoma and acute myeloid leukaemia. [16][17][18][19] Overexpressed miR-194-5p in non-small-cell lung cancer suppresses cell migration, invasion and metastasis. 20 These reports indicate that miR-194-5p functions as a tumour suppressor in various human malignancies.…”
mentioning
confidence: 99%
“…While some of the miRNAs work as oncogenes, others work as tumor suppressors [120]. For instance, it has been shown that the balance between miR-194-5p and its target BCL2-associated transcription factor 1 (BCLAF1) is commonly deregulated in AML patients [18]. Also, miR-10a-5p was found to be overexpressed in relapsed AML cases [121].…”
Section: Micro Rnasmentioning
confidence: 99%
“…miR-194-5p was reported to be down-regulated in hypopharyngeal carcinoma, acute myeloid leukemia, bladder cancer and glioblastoma and functioned as a tumor suppressor. [25][26][27] Interestingly, Yang et al found that miR-194-5p was up-regulated in breast cancer tissues and silence of miR-194-5p inhibited cell proliferation and metastasis via targeting SOX17. 28 Meanwhile, decreased miR-194-5p was implicated in sunitinib resistance in human renal cell carcinoma and paclitaxel resistance in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%